The Effect of Using Crushed Boulder Aggregate on HMA Performance - Jassim, Faris M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
Shear strength of the asphalt mixture (Marshall Stability) decreases as the percentage of rounded particles increases, which makes the mixture more susceptible to Permanent Deformation. According to SORB[1] specifications revised 2004 (R9), for prepare bitumen base layer for Hawler- Perda Highway project (new direction), the max. nominal size, (25.4 mm) of aggregate at three different crushed boulders levels: 0% (all was rounded), 50%, and 100% (more than one fracture face), added to Two different asphalt penetration grade types (40-50), and (60-70) were used to prepare the specimens. Specimens were prepared a total of 108 specimens for performance evaluation tests. It has been shown that Crushed boulders mixtures have marshall stiffness value more than 250% (100% crushing), increase VMA (voids in mineral aggregate) more than 130%, and to increase the resistance of moisture damage 135% in comparison with rounded mixtures respectively.
Keywords: Crushed aggregate; HMA performance; Hot mix asphalt; Marshall design method